Perlindungan Konsumen Obat Tradisional yang Mengandung Bahan Kimia Obat di Kota Surakarta - Diniar Hapsari; Aris Prio Agus Santoso; Rina Arum Prastyanti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Article 37 Minister of Health Regulation No. 06 of 2012 regulates the prohibition of the use of medicinal chemicals in traditional medicine, however in the field traditional medicines are still found that contain medicinal chemicals. In the 2022-2023 period in Surakarta, 571 items of traditional medicine were found containing medicinal chemicals. The problem that will be discussed in this research is how to regulate the circulation of traditional medicines containing medicinal chemicals and forms of consumer protection for traditional medicines containing medicinal chemicals in Surakarta. This research is empirical research using a sociological and legislative approach. This research is qualitative in nature where data is collected through interviews which are then analyzed descriptively. From the research results, it was concluded that there are regulations regarding the distribution of traditional medicines, but these regulations have not been effectively implemented in the community. Apart from that, it is known that the POM Center in Surakarta has provided legal protection for consumers of traditional medicines containing medicinal chemicals. The form of protection provided is in the form of pre-market and post market regarding the distribution of traditional medicines, apart from that it also provides sanctions to producers who violate the provisions.